Role of lactylation modification in regulating lytic cell death - Zhang, Xiaokang; Luo, Jing; Zhang, Zhengrong; Yu, Yang; He, Jincan; Zuo, Zan; An, Ying; Xun, Lingting; Jin, Hua; Qi, Jialong; Peng, Jun (Frontiers in Oncology, 2026)
Historically, lactate has been regarded primarily as the terminal product of glycolysis. However, recent research has elucidated its critical function as an epigenetic regulator via lactylation modification. Lactylation represents a novel post-translational modification (PTM) characterized by the covalent attachment of lactyl groups to lysine residues on both histone and non-histone proteins. This modification influences protein function at transcriptional and post-translational stages, thereby forging a direct connection between lactate metabolism and epigenetic regulation. Lytic cell death (LCD) encompasses a group of inflammatory programmed cell death modalities characterized by the rupture of the plasma membrane, playing a pivotal role in the pathogenesis of various diseases. This review provides a comprehensive synthesis of recent advancements in understanding the regulatory axis between L-lactate–induced lysine lactylation (KL-la) and LCD in disease contexts. Emerging evidence suggests that KL-la modulates several LCD subtypes, including pyroptosis, ferroptosis, and NETosis, thereby influencing disease progression and clinical outcomes. Notably, the regulatory effects of KL-la are highly context-dependent. Within the tumor microenvironment, KL-la primarily inhibits LCD, thereby promoting tumor cell survival. Conversely, in non-tumor conditions such as inflammation and ischemic injury, KL-la frequently enhances LCD, leading to increased tissue damage. This review also underscores therapeutic strategies that target lactate metabolism and KL-la-related enzymes to modulate LCD. Future interventions must incorporate the pathological context, cell-type specificity, and molecular targets. The advancement of context-responsive precision strategies, such as microenvironment-activated prodrugs or cell-specific delivery systems, will be crucial for the realization of safe and effective targeted therapies.